Near-Equatorial pi2 and pc3 Waves Observed by Champ and on Samba/Magdas Stations - Stepanova, M (Elsevier Ltd, 2015)
We have examined simultaneous ULF activity in the Pi2 and Pc3 bands at the near-equatorial magnetic stations in South America from SAMBA and MAGDAS arrays and low-orbiting CHAMP satellite during its passage over this meridional network. At the nighttime, both Pi2 and Pc3 waves in the upper ionosphere and on the ground are nearly of the same magnitude and in-phase. At the same time, the daytime Pc3 pulsations on the ground and in space are nearly out-of-phase. Comparison of observational results with the theoretical notions on the MHD wave interaction with the system ionosphere-atmosphere-ground suggests that nighttime low-latitude Pi2 and Pc3 wave signatures are produced by magnetospheric fast compressional mode. The daytime near-equatorial Pc3 waves still resist a quantative interpretation. These waves may be produced by a combination of two mechanisms: compressional mode leakage through the ionosphere, and by oscillatory ionospheric current spreading towards equatorial latitudes. © 2014 COSPAR. Published by Elsevier Ltd. All rights reserved.